Glycemia in patients with type 2 diabetes during inpatient treatment for acute myocardial infarction: impact on prognosis - M. A. Korotina; I. G. Pochinka; A. A. Frolov; S. N. Botova; L. G. Strongin (Российский кардиологический журнал, 2021)
Aim. To investigate the relationship between abnormal glycemia levels during inpatient treatment for acute myocardial infarction (AMI) in patients with type 2 diabetes (T2D) and long-term prognosis.Material and methods. The single-center cohort study included patients with AMI and concomitant T2D who were hospitalized consecutively for 200 days. A total of 237 patients were included. The median number of blood glucose measurements during hospitalization was 15 [8; 20] times. Long-term outcome was estimated at 365 days after hospitalization.Results. The first glycemic value on admission was 13,6±5,9, while the average glycemia during hospitalization was 10,0±3,5 mmol/L. Within 12 follow-up period, 53 deaths were recorded. It was found that exceeding the glycemic threshold of 10,0 mmol/L in more than 45% of measurements during hospitalization was associated with a 3-fold increase in the risk of an unfavorable outcome within 12 months. Predictors of poor glycemic control are insulin therapy before MI and blood glucose at admission >12,1 mmol/L.Conclusion. Poor glycemic control (>45% of glucose measurements above the threshold of 10,0 mmol/L) during hospitalization for AMI in patients with T2D is associated with an increased risk of in-hospital death and during the next 12 months, including in patients who underwent endovascular treatment.